Facile synthesis and excellent catalytic performance of nitrogen-doped porous carbons derived from banana peel towards oxygen reduction reaction. (July 2018) - Kong, Dewang; Liu, Lexin; Yuan, Wenjing; Xie, Anjian; Shen, Yuhua
Graphical abstract: This work demonstrates a successful example for turning discarded rubbish into valuable functional products as well as addresses the disposal issue of waste biomass and contributes to environment cleaning. And the typical sample exhibits excellent catalytic performance, high four-electron route selectivity, methanol tolerance and long-term stability toward ORR, which is comparable or even superior to Pt/C. Highlights: This work demonstrates that rubbish can convert into valuable products and addresses the disposal issue of waste biomass. The typical composite exhibits considerable catalytic activity which is comparable to Pt/C. This method was accessible and an effective strategy for the large scale application of FCs. Abstract: In this paper, nitrogen-doped porous carbons have been synthesized by using a facile low-cost and accessible approach. The banana peels which regarded as discarded rubbish were reused and acted as carbon source. The typical sample possesses plenty of interconnected pores, and its BET surface area is as large as 1442 m 2  g −1 . Electrochemical measurements indicates that the typical samples exhibits considerable catalyticactivity and high four-electron route selectivity, which is comparable or even superior to Pt/C in alkaline and acid mediums. Excitingly, the typical sample can even endure methanol-poisoning effect, and long term electrolytic corrosion with only 9.41% current density attenuation after 5000 consecutive cycles, which exceeds the performance of Pt/C in alkaline mediums. What's more, this work demonstrates a successful example for turning discarded rubbish into valuable functional products as well as addresses the disposal issue of waste biomass and contributes to environment cleaning.